Habit Protokol Kesehatan Keluar Masuk Rumah dalam Pencegahan Covid-19 oleh Masyarakat di Kelurahan Kenali Besar Kota Jambi - Armina Armina; Dwi Kartika Pebrianti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
The increase in Covid-19 cases has now reached tens of millions of cases worldwide and in Indonesia itself in early February there has been an increase in cases to more than 270 thousand cases.The process of covid-19 transmission is quite fast, namely transmission between humans so that this pandemic cannot end because humans will always have mobility from one place to another. The protocol for oneself also needs to be built in a habit, especially when going in and out of the house because of having to work or have an urgent need. Community service activities are carried out in the form of health protocol education in and out of prevention of Covid-19 and provision of covid-19 prevention equipment which is carried out in RT 30 of KenaliBesar Village to 10 residents within the period of implementation from October to February 2021. Service activities include education, demonstrations, giving booklets, giving masks, handsanitizers and tissues. Before education, residents had high knowledge and habits as well as after education. However, some understanding and increasing better habits need to be realized by residents so that family members can avoid Covid19. Residents are quite enthusiastic and will try to familiarize themselves with health protocols in and out of the house so that family members can avoid Covid19